Building Blocks And Processes For Establishing Knowledge Societies In Sub-Saharan Africa - Biao, Idowu; Tladi, Flora; Mosweunyane, Dama (Advances in Social Sciences Research Journal, 2019)
After establishing the undeniable importance of knowledge as ingredient for happy living in the 21st century, this paper probes into the pertinent question ‘which types of knowledge may guarantee the sustainable development of Sub-Saharan Africa?’. The paper argues that the establishment of the modern knowledge society (all human societies having been eternal learning or knowledge societies) is linked to the modern concept of globalisation whose core mission is to promote learning and the knowledge of the new world economic order established and advertised from the North. After highlighting the nefarious effects of uncritical adoption of Western concept of knowledge society, the paper advises that while it is proper for Sub-Saharan Africa to share in knowledge advertised by the North, that which would guarantee sustainable development of Africa is a critical integration of pieces of knowledge drawn from both the Global North and the Global South.